Factors Related to Community Participation in Independent JKN in Galang Subdistrict Deli Serdang District - Harahap, Dwi Djulhid Ashari (Jurnal Kebijakan Kesehatan Indonesia, 2025)
The coverage of participation in the Jamiman Kesehatan Indonesia (JKN) indicates that 90.98% of the population in Galang has enrolled in the JKN program. However, there remains a gap of 7.02% to achieve the Universal Health Coverage (UHC) target of 98%. Preliminary surveys of the community not participating in JKN revealed several reasons for non-participation, including lack of information, economic constraints, a perception of being healthy, and dissatisfaction with services. This study aims to identify the factors associated with community participation in independent JKN in Galang District, Deli Serdang Regency. The research employs a quantitative method with a cross-sectional design. The study population includes all residents of Galang District, involving 101 respondents obtained through purposive sampling techniques. Keramat Gajah Village was purposively selected as the research location due to its lowest independent JKN participation rate (30.62%) among other villages. Bivariate analysis results indicate significant relationships between education (p<0.001), occupation (p=0.001), income (p<0.001), number of family members (p=0.004), knowledge (p<0.001), attitude (p<0.001), perception (p=0.008), and satisfaction with services (p=0.001). It is recommended that local governments, in collaboration with BPJS Kesehatan, formulate a subsidy program for near poor groups who do not fall into the PBI category but lack adequate financial capacity. This can be achieved through assistance with partial premium costs or flexible payment schemes to prevent the community from being trapped in a situation without national health insurance protection.